Hyperosmotic cold shock mouse melanoma cells encapsulated with doxorubicin for targeted treatment of melanoma - Kong, Weihui; Wang, Chengran; Wang, Hui; Liu, Haiou; Mu, Jianhui; Jiang, Jinlan; Zhang, Congxiao (Frontiers in Oncology, 2024)
Background: The primary treatment strategies for melanoma include surgical excision, chemotherapy, and radiotherapy. However, the efficacy of these treatments is often limited by drug resistance, recurrence, and severe side effects. Therefore, we aimed to develop a targeted drug delivery system capable of selectively locating tumor sites to minimize systemic toxicity and enhance therapeutic efficacy. This cell drug delivery system can also deliver chemotherapeutic drugs to the tumor microenvironment.We treated B16F10 cells with hyperosmotic cold shock (HCS) to obtain and characterize HCS cells. We then investigated the anti-tumor effects and immune activation capabilities of these cells and explored their potential as a targeted drug delivery system.Results: HCS cells not only maintained an intact cellular structure and tumor antigens but also exhibited high expression of the homologous melanoma-associated antigen glycoprotein 100. These cells demonstrated an exceptional capacity for loading and releasing doxorubicin, which has chemotherapeutic anti-tumor effects. HCS cells can precisely target the tumor microenvironment to minimize systemic toxicity, inducing an immune response by activating CD3+ and CD4+ T cells.HCS cells are non-carcinogenic, with both cellular and tumor antigens intact; thus, they are suitable drug delivery carriers. Our findings highlight the potential of HCS cells for carrying 2 doxorubicin because of their high drug-loading efficiency, effective tumor-targeting and anti-tumor effects. Therefore, our results will facilitate the development of melanoma treatments that have higher efficacy than those in the literature.